FAMILIAL ADENOMATOUS POLYPOSIS LEADING TO ADENOCARCINOMA: A CASE ANALYSIS - Adi Arianto; Meira Dewi Kusuma Astuti; Devia Eka Listiana; Kasno (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background : Familial adenomatous polyposis (FAP) is a rare autosomal dominant disorder characterized by the development of hundreds to thousands of adenomatous polyps in the colon and rectum. Its incidence is estimated between 1 in 7,000 and 1 in 30,000 live births, accounting for less than 1% of all new cases of colorectal cancer. If left undiagnosed and untreated, nearly 100% of FAP cases progress to colorectal cancer, often by the age of 40-50. Case Description : A 55-year-old male presented with complaints of abdominal pain and a palpable mass in the abdominal region. Diagnostic colonoscopy revealed numerous sessile polyps, exceeding 100 in count, located primarily in the ascending colon. A total colectomy was performed. Histopathological examination of the resected specimen revealed: Macroscopic Findings: A white, endophytic mass in the ascending colon and over 100 sessile polyps. Microscopic Findings: Tubular adenomas with moderate dysplasia and a focus of well-differentiated adenocarcinoma. Seventeen mesenteric lymph nodes were examined and found free of metastatic involvement. Discussion : FAP is primarily caused by mutations in the APC gene, located on chromosome 5q22, which is essential for regulating cell growth and apoptosis. Loss of function in this gene leads to uncontrolled proliferation of epithelial cells in the colon, resulting in the formation of numerous polyps. Without intervention, this predisposes individuals to colorectal carcinoma. In this patient, the clinical, macroscopic, and microscopic findings strongly suggest that the adenocarcinoma developed secondary to FAP. However, a definitive diagnosis requires genetic confirmation of an APC gene mutation. Screening of family members is critical to identify asymptomatic carriers who may benefit from prophylactic interventions. Conclusion : The diagnosis of well-differentiated adenocarcinoma in the ascending colon in this patient is highly suggestive of progression from FAP. While clinical, macroscopic, and histological evidence supports this conclusion, genetic analysis of the APC gene mutation is essential for confirmation. Early detection and management of FAP, including regular surveillance and prophylactic colectomy, are paramount in preventing the development of colorectal carcinoma. Keywords: Familial Adenomatous Polyposis, Adenocarcinoma, APC Gene Mutation, Colorectal Cancer.